The impact of socio-cultural background on management and business practices of selected small and medium scale business in Sri Lanka - De Alwis, W.P.G.; Senathiraja, R. (My University, 2012)
Unlike large scale organizations many small and medium scale organizations are owned and managed by the owner himself. Hence there is a probability that the socio- cultural background (personal factors) of the owner affects his management and business practices. Many westerners argue that due to the globalization, gaps that prevailed in management and business practice between the east and the west have been significantly reduced today, and some religious values in Buddhism and Hinduism are not positive for the development of business performance. Although there were several studies which focused only on the impact of economic and political aspects few studies have focused on the impact of socio- cultural aspects on management and business practices. Studies comparing business performance of different ethnic groups and the impact of socio – cultural factors on their business performance are rare. Hence there is a significant research gap on the area of this study. The main objectives of this research were to examine whether there are differences between Sri Lankan businessmen and western management and business practices, whether Sri Lankan businessmen have developed their own business practices, and how social cultural factors have influenced their management and business practices. The analysis was based in the information collected from 150 businessmen in Textile and Jewelry industries located in urban areas. The questionnaire survey and case study methods were used to collect information. Multiple regression technique was used in data analysis. The findings of the research revealed that still there is a significant gap between the management and business practices of Sri Lankan (the east) and west and that sociocultural factors play an important role in determining management and business practices, and among all these factors religion and feminine traits are the most dominant and having a more positive effect rather than negative. There are many unique management and business practices developed and implemented by Sri Lankan entrepreneurs themselves.